Infantile Masturbation in a Nigerian Child: A Case Report of a Rare Seizure Mimic - Ubuane PO; Salisu MA; Oyinlade AO; Akinola AO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Infantile masturbation is a benign, paroxysmal, non-epileptic condition with stereotypic stiffening of the body/limbs, copulatory-like thrusting/rocking of the pelvis and somatosensory symptoms. It usually occurs without direct genital stimulation thus, making it easily misdiagnosed as epilepsy. A 12-month-old girl presented with a one-month history of 'jerking' with no fever or altered consciousness. The event usually stopped with distraction. The frequency and duration of events worsened progressively. Epilepsy was suspected initially but a subsequent review of a video recording showed a conscious female child with intermittent rhythmic rocking/thrusting of the pelvis while lying prone, making epilepsy unlikely. Infantile masturbation was diagnosed and the parents were counselled on behavioural therapy (distractions). The frequency and duration of the events progressively declined until complete resolution by six years of age. The characteristics of the events remained similar overtime except for occasional tucking of her clothes into her vagina at age five years. This report is accompanied by a review of the relevant literature on infantile masturbation.